Parental height and the sex ratio - Jean-Louis Arcand; Matthias Rieger (Graduate Institute of International and Development Studies, 2010)
This paper tests the generalized Trivers Willard hypothesis, which predicts that parents with heritable traits that increase the relative reproductive success of males compared to females will have relatively more males than females. As in Kanazawa (2005) we test if taller mothers have relatively more sons in a pooled sample of Demographic Health Surveys (DHS) from 46 developing countries. Despite using a rich dataset and an array of statistical models that address some of the concerns raised by Gelman (2007), we provide further evidence against the hypothesis.
Keywords: 330; evolutionary psychology; sex ratio; generalized Trivers Willard Hypothesis (gTWH); height; Sexualität; Körpergewicht; Psychologie; Entwicklungsländer; Welt